Many paths lead chromatin to the nuclear periphery. (8th June 2015) - Gordon, Molly R.; Pope, Benjamin D.; Sima, Jiao; Gilbert, David M.
<x xml:space="preserve">Abstract</x> It is now well accepted that defined architectural compartments within the cell nucleus can regulate the transcriptional activity of chromosomal domains within their vicinity. However, it is generally unclear how these compartments are formed. The nuclear periphery has received a great deal of attention as a repressive compartment that is implicated in many cellular functions during development and disease. The inner nuclear membrane, the nuclear lamina, and associated proteins compose the nuclear periphery and together they interact with proximal chromatin creating a repressive environment. A new study by Harr et al. identifies specific protein–DNA interactions and epigenetic states necessary to re‐position chromatin to the nuclear periphery in a cell‐type specific manner. Here, we review concepts in gene positioning within the nucleus and current accepted models of dynamic gene repositioning within the nucleus during differentiation. This study highlights that myriad pathways lead to nuclear organization.